Traditionally Used Sideritis cypria Post.: Phytochemistry, Nutritional Content, Bioactive Compounds of Cultivated Populations - Lytra, Krystalia; Tomou, Ekaterina-Michaela; Chrysargyris, Antonios; Drouza, Chryssoula; Skaltsa, Helen; Tzortzakis, Nikolaos (Frontiers in Pharmacology, 2020)
Sideritis species are recognized as important medicinal plants and their commercial demand is continuously on the rise both in the European and in the global market. Consequently, the cultivation of Sideritis species has been occurred to successfully meet the need for mass production of high-quality plant material. The present study was undertaken in order to investigate the chemical composition of cultivated S. cypria. Infusions of flowers and leaves were prepared separately, according to the European Medicine Agency (EMA) monograph. The infusion of the flowers revealed the presence of four flavones, isoscutellarein-7-O-[6′″-O-acetyl-β-D-allopyranosyl-(1→2)-β-D-glucopyranoside, its 4′-O-methyl-derivative, 4′-O-methyl-hypolaetin-7-O-[6′″-O-acetyl-β-D-allopyranosyl-(1→2)-β-D-glucopyranoside, and isoscutellarein-7-O-[6′″-O-acetyl-β-D-allopyranosyl-(1→2)]-6″-O-acetyl-β-D-glucopyranoside; four phenylethanoid glucosides, acteoside, leucosceptoside A, lamalboside, and leonoside A; one iridoid, melittoside, and one phenolic acid, chlorogenic acid, while the infusion of the leaves of the same population afforded the same first two flavones; five phenylethanoid glucosides, acteoside, leucosceptoside A, lavandulifolioside, leonoside A, and lamalboside; melittoside and chlorogenic acid. The structural elucidation of the isolated compounds was undertaken by high-field NMR spectroscopy. Moreover, the essential oils of the flowers and leaves were studied by GC-MS, separately. In addition, the mineral, bioactive compounds, protein and carbohydrate contents were evaluated for both plant materials.